Subjectivity in the interpretations of financial performance - V. Tkachuk, Natalya (2019)
The article provides an analysis of dynamic profit (income from operations) and examines the methods of its generation. The distribution of expenses by periods and corporate accounting policies have been identified as subjective factors affecting this indicator. The static interpretation of the financial performance of an organization (return on investment) has been analyzed. The concepts of capital maintenance  recommended by IFRS have been reviewed in the context of their application in Russia, taking into account the effect of inflation. It has been concluded that in Russia neither static nor dynamic profit is formed in its pure form. The study is based on the analysis of fundamental accounting assumptions (the theories of static and dynamic balance-sheet), research papers on accounting, and the legislation of the Russian Federation governing the business activities of legal entities. The study has justified the use of both dynamic and static profits in the creation of financial statements and proposed a way to represent these data in a single reporting format.